Effects of varying doses of tramadol on ketamine anaesthesia for laparocaecectomy in layer chickens (2015)
The effects of a high ketamine dose (15 mg/kg) and a low ketamine dose (10 mg/kg) combined with two separate doses of tramadol (10 and 5 mg/kg) were studied in chickens. Seventeen layer chickens (Isa brown breed) presented for laparo-cecectomy associated with feed trials were randomized into Ketamine-Lignocaine (KL) group (15 mg/kg ketamine)- 5 chickens, Tramadol-Ketamine-Lignocaine (TKL) group (10 mg ketamine plus 5 mg/kg tramadol)- 5 chickens and Tramadol-2-Ketamine-Lignocaine (TTKL) group (10 mg ketamine plus 10 mg/kg tramadol)- 7 chickens. All chickens had 2% lignocaine incision site infiltration to provide additional analgesia. Onset of drug action (OAN), Duration of recumbency (DR), heart rates (HR), respiratory rates (RR) and cloacal temperature (CT) were evaluated as anaesthetic monitoring indices. The trend for OAN was KL (3.3±0.4 min) >TKL group (4.0±3.0 min) > TTKL group (8.2±2.5 min). DR was KL group (110.3±20.8 min) > TTKL group (81.2±5.5 min) > TKL group (62.6±4.7 min). The mean variation of pre-anaesthetic and anaesthetic values of HR was not significant, although the KL group had the lowest HR. Observed fall in RR with TTKL < TKL< KL was not significant (P>0.05) among the groups. A statistically none significant (P>0.05), none life threatening fall in temperature was also observed among the groups. In the absence of inhalatory anaesthesia, 10 mg/kg ketamine combined with tramadol (5-10 mg/kg) and lignocaine infiltration may be a preferred anaesthetic protocol for non-protracted surgical procedures in chickens